Analisis Strategi Produk Usaha Keripik Dangke Melona di Desa Cendana Kecamatan Cendana Kabupaten Enrekang - Potton, Zainal; Nuha, Uli; Nasir, Alda (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze the product strategy of the Dangke Melona Chips business located in Cendana Village, Cendana Sub-district, Enrekang Regency. The research focuses on identifying competitive advantages, product development, and marketing approaches undertaken by the business. A qualitative descriptive approach was used, with data collected through interviews, observations, and documentation. The findings indicate that Dangke Melona Chips has significant potential to enhance competitiveness through product innovation, stronger branding, and market expansion. Proposed strategies include flavor diversification, more appealing packaging, and the use of digital media for marketing. By implementing these strategies, the business is expected to improve profitability and ensure long-term sustainability.